PENGARUH RETURN ON ASSETS (ROA) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM (STUDI PADA PT. INDOSAT TBK. TAHUN 2006-2015) - Dudi Hendaryan; Muhammad Rifky Ramadhan (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2018)
indicator of the success of a country in development is the economic development resulting from various fields including natural resources, labor, capital and others who mutually support each other as a whole. In practice, this economic development requires financing from both the government and the public or the private sector. Profitability, risk level or level of company health can be known from the analysis of financial statements. This financial analysis is a way to help assess past management achievements of a company and can help predict the prospects of the company in the future. A well-crafted and accurate financial report can provide a clear picture of the results or achievements that a company has achieved over a period of time, the circumstances used to assess financial performance.